The bell jar - Plath, Silvia (New Delhi : Robin Books, 2013)
This novel--echoing Plath's own experiences as a rising writer/editor in the early 1950s--chronicles the nervous breakdown of Esther Greenwood: brilliant, beautiful, enormously talented, successful, but slowly going under, and maybe for the last time.
Keywords: Depression, Mental -- Fiction; Women college students -- Fiction. -- Suicidal behavior